Exploratory Graph Analysis of the Strengths and Difficulties Questionnaire in the Longitudinal Study of Australian Children - Ribeiro Santiago, Pedro Henrique; Manzini, Davi; Haag, Dandara; Roberts, Rachel; Smithers, Lisa Gaye; Jamieson, Lisa (My University, 2021)
In Australia, the Strengths and Difficulties Questionnaire (SDQ) has been implemented in several national studies, including the Longitudinal Study of Australian Children (LSAC). However, three previous state-level validations indicated problems with instrument dimensionality, warranting further research. To address this gap, the current study employed exploratory graph analysis to investigate dimensionality of the caregiver-completed SDQ version 4 to 10 years in a nationally representative sample of Australian children. Data were from a dual cohort cross-sequential study (LSAC) that included more than 20,000 responses. Gaussian graphical models were estimated in each study wave and exploratory graph analysis applied. Structural consistency, item stability and network loadings were evaluated. The findings provided mixed support for the original SDQ five-factor structure. The Peer Problem scale displayed low structural consistency since items clustered with the Emotional Symptoms and Prosocial behavior, generating four-dimensional structures. Implications for future use of the SDQ version 4 to 10 years in Australia are provided.
Assessment
Keywords: Childhood and child development; Health and wellbeing; Surveys and survey methodology